DEEP SIGNATURE FORGERY ANALYSIS MAKING OF LAND SALE DEED - Atika Benazir Lahaya; Shamsuddin Muchtar; Muhammad Ilham Arisaputra (Awang Long Law Review, 2023)
This study aims to analyzeWhat is the cause of forgery of signatures carried out by the client in the sale and purchase deed made by the Land Deed Making Officer.The research method used in this study is normative research using a statutory approach and a conceptual approach. This study uses primary legal materials, secondary legal materials, and non-legal materials. The collection of legal materials was carried out through library research and interviews and then analyzed prescriptively. The results of the study show that the cause of signature forgery in the sale and purchase deed made by the Land Deed Official is sourced from factors originating from the parties, factors originating from PPAT employees, and factors originating from the PPAT itself.